MiR-143 inhibits proliferation and induces apoptosis of mammary epithelial cells in dairy goat. Issue 2 (3rd March 2016) - Ji, Zhibin; Wang, Guizhi; Hou, Lei; Liu, Zhaohua; Wang, Jianmin; Chao, Tianle
ABSTRACT: MicroRNAs are a class of post-transcriptional regulators of gene expression in multicellular organisms, which play important roles in cell fate, organ morphogenesis and carcinogenesis. In the present study, we demonstrated the critical roles of miR-143 on mammary epithelial cells of dairy goat. The test results of cell count, methylthiazolyldiphenyl-tetrazolium bromide, Hoechst33342/PI (propidium iodide) and flow cytometry showed miR-143-induced G0/G1 phase arrest, inhibited proliferation and promoted apoptosis of mammary epithelial cells; the qRT-PCR test of marker genes related to cell proliferation and apoptosis, BAX and BCL-2, supported the same conclusions. Our study presents evidence that miR-143 is an important post-transcription regulator involving in mammary cells survival, and it may have a value function in mammary gland development, lactation or involution.